2011
DOI: 10.1002/jcb.23059
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin increases MMP‐3 expression in human chondrocytes through adipor1 signaling pathway

Abstract: Articular adipose tissue is a ubiquitous component of human joints, and adiponectin is a protein hormone secreted predominantly by differentiated adipocytes and involved in energy homeostasis. The adiponectin is significantly higher in synovial fluid of patients with osteoarthritis and rheumatoid arthritis. Matrix metalloproteinases (MMP)-3 may contribute to the breakdown of articular cartilage during arthritis. We investigated the signaling pathway involved in MMP-3 caused by adiponectin in human chondrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 33 publications
6
49
2
4
Order By: Relevance
“…We have previously reported that leptin [Yeh et al, 2009] and GDNF [Lu et al, 2010a] enhance migration and invasion of glioma cells by increasing MMP production. Previous reports also showed that adiponectin, an adipokine, activates AMPK activation and upregulates MMP expression [Handy et al, 2010;Kang et al, 2010;Tong et al, 2011]. Here we also found that ghrelin affects the expression of MMP in human glioma cells (Suppl.…”
supporting
confidence: 77%
“…We have previously reported that leptin [Yeh et al, 2009] and GDNF [Lu et al, 2010a] enhance migration and invasion of glioma cells by increasing MMP production. Previous reports also showed that adiponectin, an adipokine, activates AMPK activation and upregulates MMP expression [Handy et al, 2010;Kang et al, 2010;Tong et al, 2011]. Here we also found that ghrelin affects the expression of MMP in human glioma cells (Suppl.…”
supporting
confidence: 77%
“…Besides, the upregulation of matrix metalloproteinase (MMP) -1 and -13 genes expression level in fi broblast-like cell was demonstrated by Choi et al (28). The relationship between adiponectin and other MMPs (MMP-2 and MMP-3) was also showed by other researchers (29,30). However, there is no investigation apart from our data to demonstrate the putative effect of adiponectin on ADAMTSs gene expression level in literature.…”
Section: Discussionsupporting
confidence: 50%
“…It can regulate the enzymatic activity of other MMPs such as MMP-1 and MMP-9, and promote collagen degradation, extracellular matrix destruction, and joint swelling, to reduce resistance to external force. With the help of the stress load, it can cause cartilage destruction (Choi et al, 2009;Tong et al, 2011). Our study showed that MMP-3 levels were significantly elevated in articular cartilage lesions.…”
Section: Discussionmentioning
confidence: 59%
“…It also causes the stagnation of the physiological metabolism of cartilage cells, causing cartilage degeneration and joint dysfunction. There are several theories about articular cartilage degeneration caused by abnormal stress (Honsawek and Chayanupatkul, 2010;Tong, 2011), which are outlined as follows:…”
Section: Discussionmentioning
confidence: 99%